Impact of electro-activation on antioxidant properties of defatted whey. (February 2017) - Kareb, Ourdia; Gomaa, Ahmed I.; Champagne, Claude P.; Jean, Julie; Aïder, Mohammed
Abstract: Antioxidant activity of electro-activated whey (EA-whey) was investigated. The effects of electric current intensity (400, 500 or 600 mA) and whey total solids concentration (7, 14 or 21%, w/v) as a function of reaction time (0, 15, 30 or 45 min) on antioxidant properties of defatted whey were studied. The extent of current intensity and reaction times were the most significant parameters ( P < 0.001). Oxygen radical absorbance capacity and 2, 2-diphenyl-1-picrylhydrazyl and hydroxyl radical scavenging activities of the EA-whey were significantly increased by the formation of Maillard reaction products (MRPs). Moreover, EA-whey possessed reducing power and strong Fe 2+ chelating ability. The MRPs derived from the EA-whey with 14% total solids concentration had the highest hydroxyl radical scavenging activity. The findings indicate the potential of electro-activation technology to enhance the functional proprieties of whey; EA-whey could be used in the food industry as a natural antioxidant ingredient to replace synthetic antioxidants.